Studying the neuroprotective role of bone marrow-derived mesenchymal stem cell secretome using in vitro and in vivo models of Parkinson’s disease - Pinheiro, Bárbara Filipa Mendes (2022)
Tese de doutoramento em Ciências da Saúde